Republic of Azerbaijan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper uses a bank-level panel dataset to investigate the determinants of bank interest spreads in Azerbaijan over 2002-2013. The dealership model of Ho and Saunders is applied, supplemented by market structure and macroeconomic environment variables, to assess the extent to which high spreads of banks in Azerbaijan can be related to bank-specific variables or to a low degree of competition, controlling for macroeconomic factors. It is found that interest spreads are affected by operation cost efficiency, credit risk, liquidity risk, bank size, bank diversification, banking sector competition, policy rate, and reserve requirement.